Regulating Mergers and Acquisitions of U.S. Electric Utilities - Hempling, Scott (Edward Elgar Publishing, 2020)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. What happens when electric utility monopolies pursue their acquisition interests-undisciplined by competition, and insufficiently disciplined by the regulators responsible for replicating competition? Since the mid-1980s, mergers and acquisitions of U.S. electric utilities have halved the number of local, independent utilities. Mostly debt-financed, these transactions have converted retiree-suitable investments into subsidiaries of geographically scattered conglomerates. Written by one of the U.S.'s leading regulatory thinkers, this book combines legal, accounting, economic and financial analysis of the 30-year march of U.S. electricity mergers with insights from the dynamic field of behavioral economics.